2008
DOI: 10.1111/j.1365-2761.2008.00909.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression and immunogenic comparison of VP2 and VP3 from marine birnavirus

Abstract: The coding regions for the major epitopes of structural protein VP2 (vp2e) and structural protein VP3 were amplified from marine birnavirus (MABV) cDNA and efficiently expressed as glutathione S-transferase (GST) fusion proteins in Escherichia coli. Polyclonal antibodies against VP2e and VP3 were raised in rabbits and fish using the purified proteins of GST/VP2e and GST/VP3. The rabbit anti-serum against VP3 was more sensitive than the rabbit anti-VP2e serum in detecting virus in MABV-infected fish, while fish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…The results showed that the rOmp-G had good immunogenicity for eliciting good humoral immune responses both in rabbits ( Table 2) and in eels (Fig. 5), which was in accordance with other studies [33,34]. All the results showed that the rGST-His tag did not affect the immunogenicity and specificity of the rOmp-G. At the same time, the results also showed that the rOmp-G was recognized by the rabbit antisera ( Table 2), as well as by the eel anti-sera (Fig.…”
Section: Discussionsupporting
confidence: 79%
“…The results showed that the rOmp-G had good immunogenicity for eliciting good humoral immune responses both in rabbits ( Table 2) and in eels (Fig. 5), which was in accordance with other studies [33,34]. All the results showed that the rGST-His tag did not affect the immunogenicity and specificity of the rOmp-G. At the same time, the results also showed that the rOmp-G was recognized by the rabbit antisera ( Table 2), as well as by the eel anti-sera (Fig.…”
Section: Discussionsupporting
confidence: 79%
“…Mai et al / Veterinary Parasitology xxx (2015) xxx-xxx 7 depend on host specificity. C. irritans predominantly infects marine fish species rather than rabbit, mouse or any other mammal, and the immune responses of fish generated from infection by C. irritans are stronger in intensity and of longer duration than those of other animal against heterologous protein extracted from C. irritans (Xu et al, 2008). Meanwhile, actin showed common immunogenicity in all three rabbit anti-sera, and ␤-tubulin of theronts was immunoreactive with rabbit and grouper anti-sera, suggesting that these two proteins might be strongly reactive to the host immune system.…”
Section: Discussionmentioning
confidence: 99%